Geliat Puritanisme Islam di Indonesia: Menyibak Tabir di Balik Gerakan Majelis Tafsir Al-Qur’an (MTA) dalam Perspektif Sosiologis - Ilyya Muhsin; Muhammad Ghufon (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2018)
Islamic purification movement which run by MTA (Majelis Tafsir Al-Qur'an; Quranic interpretation council) is an interesting one to be discussed. MTA, an institution with the charismatic leader, is preaching Islam puritanically like other Islamic organizations which have active branches with organized structure in every level. Therefore, this article will discuss MTA movement in sociological perspective, particularly using social movement theory. The results can be seen in three social movement types. The first type is to use political opportunities through a national gathering forum (Silatnas) and Sunday Morning Preaching (Pengajian Ahad Pagi). The second type is to mobilize all capitals; moral resources include Quran-Sunnah as well as charisma of the leader; cultural resources includes all MTA's religious business; human resources with structured cadre system, well-organized social-organization resources; and excessive economic resources. The last type is to frame its religious movement to resolve every Islamic-social pathology through the best method on MTA perspective